Can p-values be meaningfully interpreted without random sampling? - Norbert Hirschauer; Sven Grüner; Oliver Mußhoff; Claudia Becker; Antje Jantsch (Statistics Surveys, 2020)
Besides the inferential errors that abound in the interpretation of p-values, the probabilistic pre-conditions (i.e. random sampling or equivalent) for using them at all are not often met by observational studies in the social sciences. This paper systematizes different sampling designs and discusses the restrictive requirements of data collection that are the indispensable prerequisite for using p-values.
Keywords: C10; C83; 330; sampling design; propensity scores; p-values; random sampling; selection bias; inference